2015
DOI: 10.1128/aac.01073-15
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of liaR Reverses Daptomycin Resistance in Enterococcus faecium Independent of the Genetic Background

Abstract: fWe have shown previously that changes in LiaFSR, a three-component regulatory system predicted to orchestrate the cell membrane stress response, are important mediators of daptomycin (DAP) resistance in enterococci. Indeed, deletion of the gene encoding the response regulator LiaR in a clinical strain of Enterococcus faecalis reversed DAP resistance (DAP-R) and produced a strain hypersusceptible to antimicrobial peptides. Since LiaFSR is conserved in Enterococcus faecium, we investigated the role of LiaR in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 39 publications
0
41
0
1
Order By: Relevance
“…To determine whether c-di-AMP signaling is present in other enterococcal strains, daptomycin-tolerant and vancomycin-resistant Enterococcus faecium clinical isolate HOU503 and its fusidic acid-resistant derivative E. faecium HOU503F were tested (Table 1) (27). The c-di-AMP levels of E. faecium HOU503 and E. faecium HOU503F were 766 Ϯ 318 and 542 Ϯ 133 pM/OD 600 at late exponential phase (OD 600 , ϳ1.2) ( Table 1 and Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To determine whether c-di-AMP signaling is present in other enterococcal strains, daptomycin-tolerant and vancomycin-resistant Enterococcus faecium clinical isolate HOU503 and its fusidic acid-resistant derivative E. faecium HOU503F were tested (Table 1) (27). The c-di-AMP levels of E. faecium HOU503 and E. faecium HOU503F were 766 Ϯ 318 and 542 Ϯ 133 pM/OD 600 at late exponential phase (OD 600 , ϳ1.2) ( Table 1 and Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To demonstrate that changes in LiaFSR signaling lead to changes in c-di-AMP more broadly, we measured the c-di-AMP levels in nonpolar liaR deletion mutants of E. faecium strains HOU503F and R497F (E. faecium HOU503F_ΔliaR and R497F_ΔliaR, Table 1) which are tolerant of and resistant to daptomycin (27). As observed with E. faecalis, deletion of liaR in E. faecium HOU503F_ΔliaR and R497F_ΔliaR showed modest increases in c-di-AMP levels compared to E. faecium HOU503F and R497F (622 Ϯ 104 pM/OD 600 versus 542 Ϯ 133 pM/OD 600 and 736 Ϯ 186 pM/OD 600 versus 549 Ϯ 150 pM/OD 600 , Fig.…”
Section: C-di-amp Signaling In Enterococcimentioning
confidence: 99%
“…It is also significant that genes protective against daptomycin (liaXYZ) are highly upregulated in response to chlorhexidine. It was recently demonstrated that deletion of liaR, encoding an activator of liaXYZ expression (45), restores daptomycin susceptibility to daptomycin-nonsusceptible enterococci (76). Further studies will be required to determine whether gene expression "priming" by chlorhexidine impacts treatment outcomes with daptomycin, or if frequent exposure to subinhibitory chlorhexidine is selective for strains that constitutively activate liaXYZ.…”
Section: Discussionmentioning
confidence: 99%
“…116 In such strains, the activation of LiaRS greatly reduces the efficiency of daptomycin to bacterial cells. 117 When activated, LiaRS induces the expression of LiaI and LiaH, which colocalize within segregated domains in the cytoplasmic membrane. 118 The phenotypic effects of these effector molecules, and accordingly their role in daptomycin resistance, are not yet understood.…”
Section: Activation Of Liarsmentioning
confidence: 99%